Multiply repeated reverse transcriptase PCR (MR-RT-PCR) as a new method to diagnose residual neoplastic disease in malignant melanoma and potentially in other tumors - Szenajch, Jolanta; Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2003)
Molecular diagnosis of cancer is gradually shifting towards diagnosis of minimal disease i. e. disease that avoids detection and investigation using classical methods. Introduction of RT-PCR allowed to detect individual cancer cells in tested sample of blood or tissue and to lower the limit of detection to about 103 in the entire blood. However, release of 1000 cells to the blood may be for many tumors an extremely rare event and such situation requires yet more sensitive methods. The problem became particularly controversial in malignant melanoma, where results of molecular investigations appeared not to correlate with the disease stage. Studies performed by our group have been used to verify a hypothesis that it was due to the fact that the number of circulating melanoma cells (CMCs) is and fluctuates in the course of the disease significantly below the lowest detection level of RT-PCR. Therefore, on average, in the early disease only one out of five samples tests positive (approximately 200 CMCs), while in the advanced disease, on average, one out of three samples tests positive (approximately 333 CMCs). These conclusions have been reached after employing multiply repeated tests in each patient and utilization of the appropriate statistical analyses. We have developed the most sensitive available method of diagnosis of residual disease in the peripheral blood that allows to detect even less than 100 CMCs. We termed this method multiply repeated RT-PCR or MR-RT-PCR. This method should be now explored in other neoplastic disorders such as chronic myelocytic leukemia, mantle cell lymphoma or prostate cancer. It should provide a technology to detect very rare cells, present in less than one evaluated sample, and allow to study novel aspects of neoplastic disorders.